THE PRE-MERGER EFFICIENCY OF BANKS: EVIDENCE IN INDONESIA STATE-OWNED ISLAMIC BANKS - Tyas, Atika Ayuning; Rusydiana, Aam Slamet (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2021)
In an effort to improve the development of the sharia economy in Indonesia, the Ministry of State-Owned Enterprises (BUMN) has decided to carry out a merger of BRI Syariah, Bank Syariah Mandiri, and BNI Syariah becomes Bank Syariah Indonesia. This merger plan is implemented to increase the share of the Islamic banking market so that it can compete with conventional banking. In order to be able to compete with conventional banking, Islamic banks must be able to have efficient performance and high productivity. This research is a quantitative study to analyze and compare the performance efficiency of BRISyariah, Bank Syariah Mandiri, and BNISyariah with the performance efficiency of ten conventional banks for the 2016-2019 periods using the Data Envelopment Analysis (DEA) method with five analysis models to obtain various considerations in preparing the merger plan. The estimation results show that if the three Islamic banks are merged, they will have inefficient performance with an efficiency score of 0.86. On the other hand, if only two Islamic banks are merged, namely BNISyariah and BRISyariah, it will produce perfect efficiency values.